Developing an App by Exploiting Web-Based Mobile Technology to Inspect Controlled Substances in Patient Care Units. (14th February 2017) - Lu, Ying-Hao; Lee, Li-Yao; Chen, Ying-Lan; Cheng, Hsing-I; Tsai, Wen-Tsung; Kuo, Chen-Chun; Chen, Chung-Yu; Huang, Yaw-Bin
Abstract : We selected iOS in this study as the App operation system, Objective-C as the programming language, and Oracle as the database to develop an App to inspect controlled substances in patient care units. Using a web-enabled smartphone, pharmacist inspection can be performed on site and the inspection result can be directly recorded into HIS through the Internet, so human error of data translation can be minimized and the work efficiency and data processing can be improved. This system not only is fast and convenient compared to the conventional paperwork, but also provides data security and accuracy. In addition, there are several features to increase inspecting quality: (1) accuracy of drug appearance, (2) foolproof mechanism to avoid input errors or miss, (3) automatic data conversion without human judgments, (4) online alarm of expiry date, and (5) instant inspection result to show not meted items. This study has successfully turned paper-based medication inspection into inspection using a web-based mobile device.